SOURCE ROCK CHARACTERISTICS AND THERMAL MATURITY IN JAMBI SUB-BASIN, SOUTH SUMATRA BASIN - Ambari, Wardahrose Dhifa; Ilmi, Nisa Nurul; Sunardi, Edy (Journal of Geological Sciences and Applied Geology, 2026)
The Jambi Sub-Basin, located within the South Sumatra Basin, represents one of the prospective hydrocarbon-bearing areas in Indonesia due to the presence of organic-rich syn-rift and post-rift sedimentary sequences and a well-developed petroleum system. This study aims to evaluate source rock characteristics and hydrocarbon generation potential of several stratigraphic interval in the Jambi Sub-Basin using Total Organic Carbon (TOC) and Rock-Eval Pyrolysis data obtained from fourteen wells in the study area. The analyses were conducted to assess the quantity, quality, and thermal maturity of organic matter within the source rocks. The results indicate that the Lower Talang Akar Formation (LTAF) and Upper Talang Akar Formation (UTAF) could become the most prospective source rock intervals, characterized by moderate to excellent TOC values with S2 values ranging from poor to excellent generative potential. Organic matter is primarily composed of type II-III kerogen, indicating dominant terrestrial organic matter input deposited in fluvia-deltaic to marginal lacustrine environment, with the capability to generate mixed gas and oil hydrocarbons. Hydrogen Index (HI) values range from 14 to 561 mg HC/ g TOC, reflecting variable organic matter quality and depositional conditions across the basin. Thermal maturity parameters, including Tmax and vitrinite reflectance, indicate maturity levels ranging from immature to post mature stages. The Talang Akar intervals generally show higher maturity levels associated with deeper burial and prolonged thermal evolution, suggesting active hydrocarbon generation, particularly gas generation in the deeper areas. The integration of organic richness, kerogen type, and maturity distribution suggests that the LTAF represents the principal gas-prone source rock within the study area, while several intervals still has their oil-generation potential. This study could provide an integrated organic geochemical framework for evaluating source rock distribution in the Jambi Sub-Basin and contribute to the improvement of future hydrocarbon exploration strategies in the South Sumatra Basin.Keyword: source rock, Rock-Eval Pyrolysis, Talang Akar Formation, Thermal Maturity, South Sumatra Basin